2012
DOI: 10.1515/cclm-2012-0048
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in primary open angle glaucoma

Abstract: Glaucoma, a leading cause of blindness worldwide, is currently defi ned as a disturbance of the structural or functional integrity of the optic nerve that causes characteristic atrophic changes in the optic nerve, which may lead to specifi c visual fi eld defects over time. This disturbance usually can be arrested or diminished by adequate lowering of intraocular pressure (IOP). Glaucoma can be divided roughly into two main categories, ' open angle ' and ' closed angle ' glaucoma. Open angle, chronic glaucoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 103 publications
1
18
0
4
Order By: Relevance
“…Elevated IOP is the most commonly identified ocular risk factor in the development of glaucomatous optic neuropathy, and trabecular meshwork cells play an important role in the regulation of aqueous outflow and IOP. Although IOP is the only treatable risk factor for glaucomatous optic neuropathy, including XFG, there is little doubt that other factors play a role 140,141 . Interestingly, some patients acquire damage before they suffer from an increase in IOP.…”
Section: Contribution Of Oxidation Stress In Xfg Pathobiology and Conmentioning
confidence: 99%
“…Elevated IOP is the most commonly identified ocular risk factor in the development of glaucomatous optic neuropathy, and trabecular meshwork cells play an important role in the regulation of aqueous outflow and IOP. Although IOP is the only treatable risk factor for glaucomatous optic neuropathy, including XFG, there is little doubt that other factors play a role 140,141 . Interestingly, some patients acquire damage before they suffer from an increase in IOP.…”
Section: Contribution Of Oxidation Stress In Xfg Pathobiology and Conmentioning
confidence: 99%
“…The etiology of this disease is poorly understood. While there are obvious ocular biomarkers for POAG, such as optic nerve head excavation, neuroretinal rim erosion, and elevated intraocular pressure (IOP), 1 and recent studies have identified genetic loci that alter the risk of POAG and glaucoma-related traits, 2 there are no established systemic biomarkers. The ultimate goal for a better understanding of POAG etiology and improved POAG screening is to identify biomarkers for pathogenic factors that precede IOP elevation and optic neuropathy.…”
mentioning
confidence: 99%
“…There were significantly elevated levels of Hepcidin (HEPC) and Cystatin C (CYTC), two candidate biomarkers previously identified in primary open angle glaucoma (POAG). 8 …”
Section: Case Reportmentioning
confidence: 99%